Uji Aktivitas Ekstrak Daun Opo-Opo (Desmodium pulchellum Linn Benth) sebagai Antibakteri terhadap Pertumbuhan Streptococcus viridans dan Streptococcus pyogenes: Activity Test of Opo-Opo Leaf Extract (Desmodium pulchellum Linn Benth) as Antibacterial for the Growth of Streptococcus viridans and Streptococcus pyogenes - Dewi Isnaeni; Andi Ulfah Magefirah Rasyid; Rahmawati Rahmawati (Jurnal Sains dan Kesehatan, 2021)
Streptococcal tonsillopharyngitis is a type of tonsillopharyngitis caused by group A streptococcal bacterial infection with common symptoms such as sore throat, fever more than 38oC, tonsilar exudate, and cervical adenopathy. Possible complications of streptococcal tonsillopharyngitis include rheumatic fever that occurs at weeks 1-5 after acute respiratory infections by Streptococcus viridans and Streptococcus pyogenes. Treatment needs to be done This research aims to determine the value of Minimum Inhibitory Concentration (MIC) and Minimum Kill Concentration (MKC) of Opo-opo leaf extract (Desmodium pulchellum Linn Benth) on the growth of Streptococcus viridans and Streptococcus pyogenes. This research uses a maceration extraction method of the ingredients. microbiological test and test using the liquid dilution method. The extract concentration used was 0.1% w / v, 0.25% w / v, 0.5% w / v, 0.75% w / v, 1% w / v, 1.25% w / v , 1.5% w / v, 1.75% w / v, 2% w / v, 2.25% w / v, 2.5% w / v with negative control of Na, CMC 1% w / v. The test results showed that the MIC of Opo-opo leaf extract on Streptococcus viridans was 0.75%, MKC of opo-opo leaf extract on Streptococcus viridaans was 1% while the MIC of Opo-opo leaf extract on Streptococcus pyogenes was 0.25% and the MKC of leaf extract. Opo-opo in Streptococcus pyogenes is 1%. The results of the phytochemical screening of Opo-opo leaf extract (Desmodium pulchellum Linn Benth) were positive for alkaloids, flavonoids, tannins and terpenoids.